2010
DOI: 10.4314/sljbr.v2i1.56586
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Six-Week Aerobic Dance Programme on Selected Fitness Components and Waist-Hip-Ratio in Adult Males

Abstract: This study examined the effects of a six-week low-impact aerobic dance on selected fitness components (trunk flexibility, leg power and abdominal muscle endurance) and waist-hip-ratio (WHR) in adult males. A total of fifteen (15) Lagos State University male undergraduates (age range: 19-28 years) from the Faculty of Education volunteered to take part in the study. The one-group pre-test-post-text quasi-experimental research design was employed. Both pre-test and post-test measurements were taken from each part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Only balances of all these can help achieve total wellness. As observed by Okuneye et al, (2010) [3] in the current years, the definition of health has been stretched to include wellness; a state of being that enables the individual to reach one's fullest potential. Wellness integrates aspects such as adequate fitness, proper nutrition, stress management, disease prevention, smoking cessation, personal safety, and control on substance abuse, good level of spirituality, regular physical examinations, health education and environmental support.…”
Section: Introductionmentioning
confidence: 99%
“…Only balances of all these can help achieve total wellness. As observed by Okuneye et al, (2010) [3] in the current years, the definition of health has been stretched to include wellness; a state of being that enables the individual to reach one's fullest potential. Wellness integrates aspects such as adequate fitness, proper nutrition, stress management, disease prevention, smoking cessation, personal safety, and control on substance abuse, good level of spirituality, regular physical examinations, health education and environmental support.…”
Section: Introductionmentioning
confidence: 99%
“…As observed by Okuneye et al, (2010) in the current years, the definition of health has been stretched to include wellness; a state of being that enables the individual to reach one's fullest potential [3]. Wellness integrates aspects such as adequate fitness, proper nutrition, stress management, disease prevention, smoking cessation, personal safety, and control on substance abuse, good level of spirituality, regular physical examinations, health education and environmental support.…”
Section: Introductionmentioning
confidence: 99%
“…It has a constant intensity and is a dynamic combination of aerobic activity such as walking, marching, dancing, jogging and jumping exercise, put together in choreographed sequences (Nieman, 1993). 10 Yun (2011) 11 reported that routine aerobic dance for 12 weeks reduced Waist to Hip Ratio (WHR) in young women aged 19-21 years while Okuneye et al (2010) 12 reported 6 weeks aerobic dance reduced WHR in men. This research aimed to determine the effect of 12 weeks programmed aerobic dance on body composition parameters of young women in Purwokerto, Central Java, Indonesia.…”
Section: Introductionmentioning
confidence: 99%